2021
DOI: 10.1098/rsos.201618
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic property of silk fibroin scaffolds with adipose-derived stem cells on chick chorioallantoic membrane

Abstract: Angiogenesis is a crucial step in tissue regeneration and repair. Biomaterials that allow or promote angiogenesis are thus beneficial. In this study, angiogenic properties of salt-leached silk fibroin (SF) scaffolds seeded with human adipose stem cells (hADSCs) were studied using chick chorioallantoic membrane (CAM) as a model. The hADSC-seeded SF scaffolds (SF-hADSC) with the porosity of 77.34 ± 6.96% and the pore diameter of 513.95 ± 4.99 µm were implanted on the CAM of chick embryos that were on an embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Usually, SF scaffolds used for bone regeneration exhibit high porosity and thus allow the vessel ingrowth, which can be improved by pre-seeded cells before implantations. Watchararot et al (2021) seeded human adipose-derived stem cells (hADSC) onto SF scaffolds and implanted them into chick chorioallantoic membrane with the pore diameter of 513.96 ± 4.99 μm and porosity of 77.34 ± 6.96%. A capillary network of spoke-wheel pattern was induced by the seeded scaffolds 3 weeks earlier than unseeded scaffolds, indicating an early angiogenesis.…”
Section: Vascular Ingrowthmentioning
confidence: 99%
“…Usually, SF scaffolds used for bone regeneration exhibit high porosity and thus allow the vessel ingrowth, which can be improved by pre-seeded cells before implantations. Watchararot et al (2021) seeded human adipose-derived stem cells (hADSC) onto SF scaffolds and implanted them into chick chorioallantoic membrane with the pore diameter of 513.96 ± 4.99 μm and porosity of 77.34 ± 6.96%. A capillary network of spoke-wheel pattern was induced by the seeded scaffolds 3 weeks earlier than unseeded scaffolds, indicating an early angiogenesis.…”
Section: Vascular Ingrowthmentioning
confidence: 99%
“…ADSCs served as usual tools for vascularization in tissue engineering because of their convenient management, ability to self-renew and differentiate into various cell types, and secretion of angiogenic factors [ 31 , 32 ]. ADSCs-seeded silk fibroin scaffolds or hydrogels that accelerated angiogenesis were reported [ 33 , 34 ]. Our previous study also reported that ADSCs-seeded-PADM promoted pro-vascular gene expression and increased vascular infiltration [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…These factors are released from different stem cell types such as EPCs, MSCs, and peripheral blood mononuclear cells and have been typically used for angiogenesis evaluations in several preclinical and clinical studies [ 262 ]. In response to the gradients of angiogenic factors, EPCs, MSCs, and peripheral blood mononuclear cells are recruited from different tissues, especially bone marrow, and accommodated the injured sites [ 263 ].…”
Section: Induction Of Angiogenesis Using Scaffolds For Muscle Regener...mentioning
confidence: 99%